Self-Efficacy Training To Improve Hardiness of Firefigthers in “Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung” - Ni Luh Wayan Rai Utari; C.M. Indah Soca R.K; Robert O. Rajagukguk (PSIKODIMENSIA, 2020)
The purpose of this research is to understand the increasing of hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung after given self-efficacy training. The theory used were self-efficacy theory from Bandura (2002) and hardiness from Maddi & Khosaba (2005). The research has 18 subjects as a sample taken by purposive sampling methods. The methods use was Quasi-experimental. Data was analyzed using Wilcoxon signed rank test statistic methods to make comparison between pre-test and post-test. As a result of this research: degree of hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung was increase after participate in self-efficacy training. Conclude that self-efficacy training could help to increase hardiness in Firefighter of Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung.